Build real-world AWS microservices with Python and FastAPI from zero. (Pragmatic AI Solutions, 2022)
Build Real-World AWS Microservices with Python and FastAPI From Zero. Practice end-to-end DevOps from scratch! This video will show you how to start from the absolute beginning of DevOps and build a real-world AWS microservice with Python and FastAPI. Topics Covered Include: 00:00 Introduction 01:00 Learning to use Github CodeSpaces 03:00 Building Python Project Scaffolding 06:50 Building Python virtualenv 09:00 Adding a Python Dependency 22:58 Setup GitHub Actions 34:00 Running Pylint on your project 42:00 Using a library you created 46:00 Building library tests with Pytest 51:00 Building CLI tools with Python Fire 59:00 Using IPython with libraries 01:02:09 Exploring Python wikipedia library 01:08:00 Using FastAPI and uvicorn 01:15:00 Exploring FastAPI Swagger API docs for microservice with wikipedia library 01:18:00 Adding NLP with textblob library in Python 01:29:00 Running tests with Pytest 01:34:00 Integrating Docker with FastAPI 01:50:00 Using AWS ECR (Elastic Container Registry) with FastAPI 01:52:00 Integrating AWS CodeBuild for Continuous Delivery to ECR Learning Objectives Using AWS to build real-world microservices Deploying AWS microservices with AWS CloudBuild and AWS App Runner for FastAPI Practice end-to-end DevOps from scratch with Python and FastAPI Additional Popular Resources Pytest Master Class AWS Solutions Architect Professional Course Github Actions and GitOps in One Hour Video Course Jenkins CI/CD and Github in One Hour Video Course AWS Certified Cloud Practitioner Video Course Advanced Testing with Pytest Video Course AWS Solutions Architect Certification In ONE HOUR Python for DevOps Master Class 2022: CI/CD, Github Actions, Containers, and Microservices MLOPs Foundations: Chapter 2 Walkthrough of Practical MLOps Learn Docker containers in One Hour Video Course Introduction to MLOps Walkthrough AZ-900 (Azure Fundamentals) Quick reference guide 52 Weeks of AWS Episode 8: Infrastructure as Code with CDK and AWS Lambda Learn GCP Cloud Functions in One Hour Video Course Python Devops in TWO HOURS! MLOps Platforms From Zero: DatMLOps Platforms From Zero: Databricks, MLFlow/MLRun/SKLearn AWS Machine Learning Certification In ONE HOUR Fast, documented Machine Learning APIs with FastAPI Zero to One: AWS Lambda with SAM and Python in One Hour AWS Storage Solutions 2022: EBS/S3/EFS/Glacier Python Bootcamp for Data Testing In Python book Minimal Python book Practical MLOps book Python for DevOps-Playlist.